The Underdevelopement of EL Salvadoras Human Resources (Global Journal of Management and Business Research, 2016)
The purpose of this article is to expose the reasons for the underdevelopment of the human resources in El Salvador. The problem of underdevelopment started with the employment of the manpower in coffee plantations, a situation that did not necessitate the development of the workforce. Adverse economic conditions, poverty, bad working conditions, unemployment, underemployment, and no access to basic education added to the underdevelopment of the human element. Currently, the government is providing incentives for the education of manpower, especially in the area of small and medium-sized business organizations that make up the majority of private enterprises in the country.
Keywords: training; education; small businesses; medium businesses; large businesses; coffee plantations; coffee economy; maquiladoras; unemployment; underemplo